Kepemimpinan Kepala Sekolah Perempuan dalam Meningkatkan Kerjasama Guru: Analisis Penerapan Gaya Kepemimpinan Transformasional - Nasikhah, Khafidhotun; Maunah, Binti; Patoni, Achmad (Fitrah: Journal of Islamic Education, 2022)
This study aims to analyze the leadership of female school principals to improve teacher cooperation. The focus of the study on the application of the transformational leadership style in terms of its implementation phase. This research was conducted at Al-Huda Islamic Elementary School, for two reasons, namely the principal of the school is a woman and the image of the school is popular and very popular with the community. This study uses a qualitative method with a phenomenological approach. Data collection techniques using observation, interviews, and documentation studies. The data is then analyzed with cycles of data collection, data presentation, and drawing conclusions. The results of the study revealed that the implementation of transformational leadership in Al-Huda Islamic Elementary School went through two phases namely, first the leader was able to carry himself and fully understand being a personal leader which was implemented through: leader awareness and understanding the epistemology of leadership. Both leaders are able to influence and form cooperation with followers which is implemented through: providing work motivation, effective communication, being able to set an example, stimulate, and establish friendships.